Pandemi Covid-19 dan Implikasinya terhadap Polarisasi Mazhab Teologi di Indonesia - Amtiran, Abdon Arnolus (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
This study was carried out to analyze the symptoms that arose at the time of the covid pandemic 19. The covid pandemic 19 caused an extraordinary crisis that shook social, political and economic life. Millions of people have been exposed and hundreds of thousands lost their lives. This caused panic, stress and frustration and in the lives of many people the church members were no exception. At the same time, there is a polarization in theological schools that are present in addressing this condition. This study used a qualitative approach with a descriptive method and literature analysis. The conclusion obtained that theological schools of thought is a reality that can not be nullified because it is the same age as Christianity itself. Therefore, what is urgent to do is a concerted effort to take concrete steps in dealing with this extraordinary crisis. And also the existence of a new theological effort in the midst of the enactment of